2021
DOI: 10.3390/ma14174832
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations of Fracture Behaviour of Welded Joints with Multiple Defects

Abstract: Current standards related to welded joint defects (EN ISO 5817) only consider individual cases (i.e., single defect in a welded joint). The question remains about the behaviour of a welded joint in the simultaneous presence of several different types of defects, so-called multiple defects, which is the topic of this research. The main focus is on defects most commonly encountered in practice, such as linear misalignments, undercuts, incomplete root penetration, and excess weld metal. The welding procedure used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The results show that the presence of the internal defects in the welded Q345B steel joints depends on the stir–pin rotation speed, weld speed, and cooling intensity during welding. Mihajlo et al [ 52 ] performed both numerical and experimental studies in order to understand the fracture behaviour of welded joints with multiple defects. The results suggest that the weakness of the welded joints are due to the misalignment and incomplete root penetration and also due to the unseen internal defects.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the presence of the internal defects in the welded Q345B steel joints depends on the stir–pin rotation speed, weld speed, and cooling intensity during welding. Mihajlo et al [ 52 ] performed both numerical and experimental studies in order to understand the fracture behaviour of welded joints with multiple defects. The results suggest that the weakness of the welded joints are due to the misalignment and incomplete root penetration and also due to the unseen internal defects.…”
Section: Introductionmentioning
confidence: 99%
“…The true-stress-true-strain curves show a better prediction of the formability of the material than the agreed engineering characteristics of materials Re, tensile strength Rm, uniform tensibility, and tensibility. The actual stress can be calculated according to Equation (9) [33,38]:…”
Section: Resultsmentioning
confidence: 99%
“…The results presented in [32,33] show that the widely used standards ISO 5817 and ISO 5178 have room for innovation to meet the needs of numerical simulations. In order to take into account the material inhomogeneity of welded joints in the formability analysis in the numerical simulation of laser welded blanks, using the finite element method (FEM), the basic mechanical properties and values of the material properties necessary for the simulation of the sheet-metal forming processes were determined (strength constant K, strain hardening exponent n, and plastic strain ratio r) on specimens with a longitudinal laser weld.…”
Section: Methodsmentioning
confidence: 99%
“…From this experimental campaign, it was found that the larger specimens showed lower fatigue resistance due to the appearance of larger inclusions in the fish-eye fracture origin. In fact, it is well-known that crack nucleation in the VHCF domain is originated from the largest inclusion embedded in the risk-volume, which represents the weakest site within the highly-stressed volume [15][16][17]. Hence, since the VHCF fracture mechanism is governed by the defect population, it follows that the gigacycle fatigue strength can be related to the size of the largest defect within the risk-volume according to Murakami's model [18,19].…”
Section: Introductionmentioning
confidence: 99%